Upregulation of RGS2: a new mechanism for pirfenidone amelioration of pulmonary fibrosis. Issue 1 (December 2016) - Xie, Yan; Jiang, Haihong; Zhang, Qian; Mehrotra, Suneet; Abel, Peter; Toews, Myron; Wolff, Dennis; Rennard, Stephen; Panettieri, Reynold; Casale, Thomas; Tu, Yaping
Abstract Background Pirfenidone was recently approved for treatment of idiopathic pulmonary fibrosis. However, the therapeutic dose of pirfenidone is very high, causing side effects that limit its doses and therapeutic effectiveness. Understanding the molecular mechanisms of action of pirfenidone could improve its safety and efficacy. Because activated fibroblasts are critical effector cells associated with the progression of fibrosis, this study investigated the genes that change expression rapidly in response to pirfenidone treatment of pulmonary fibroblasts and explored their contributions to the anti-fibrotic effects of pirfenidone. Methods We used the GeneChip microarray to screen for genes that were rapidly up-regulated upon exposure of human lung fibroblast cells to pirfenidone, with confirmation for specific genes by real-time PCR and western blots. Biochemical and functional analyses were used to establish their anti-fibrotic effects in cellular and animal models of pulmonary fibrosis. Results We identified Regulator of G-protein Signaling 2 (RGS2) as an early pirfenidone-induced gene. Treatment with pirfenidone significantly increased RGS2 mRNA and protein expression in both a human fetal lung fibroblast cell line and primary pulmonary fibroblasts isolated from patients without or with idiopathic pulmonary fibrosis. Pirfenidone treatment or direct overexpression of recombinant RGS2 in human lung fibroblasts inhibited the profibrotic effects of thrombin, whereas loss of RGS2 exacerbated bleomycin-induced pulmonary fibrosis and mortality in mice. Pirfenidone treatment reduced bleomycin-induced pulmonary fibrosis in wild-type but not RGS2 knockout mice. Conclusions Endogenous RGS2 exhibits anti-fibrotic functions. Upregulated RGS2 contributes significantly to the anti-fibrotic effects of pirfenidone.